1990
DOI: 10.1111/myc.1990.33.7-8.393
|View full text |Cite
|
Sign up to set email alerts
|

The effects of amorolfine and oxiconazole on the ultrastructure of Trichophyton mentagrophytes. A comparison

Abstract: Amorolfin applied in concentrations of 0.1-100 micrograms ml-1 caused considerable damages to the ultrastructure of Trichophyton mentagrophytes: Electron-transparent areas appear in the cytoplasma. The cell wall increases in thickness. Extracytoplasmic membrane vesicles are formed and deposited in the cell wall. Starved fungal cells, with normal ultrastructure, can be found. Lysed, dead cells demonstrate the process of final, vigorous ultrastructural damage. The feature of the damage caused by amorolfin is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…5). Similar findings were described by Melchinger et al (1990) and Figueras et al (1995), which demonstrated that these electron-dense materials were due to the leakage of cytoplasmic constituents in the course of the damaging process, but not attribute to the preparation techniques of TEM. From our point of view, the fibrillar materials were most probably related to be the initial stages of CF66I-cell interactions or with the preliminary step of cell destruction, which could explain why it was almost absent in the completely destroyed hyphae (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…5). Similar findings were described by Melchinger et al (1990) and Figueras et al (1995), which demonstrated that these electron-dense materials were due to the leakage of cytoplasmic constituents in the course of the damaging process, but not attribute to the preparation techniques of TEM. From our point of view, the fibrillar materials were most probably related to be the initial stages of CF66I-cell interactions or with the preliminary step of cell destruction, which could explain why it was almost absent in the completely destroyed hyphae (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we quantified C. albicans actin mRNA as a means of assessing the viability of C. albicans in a reconstituted-human-skin model of cutaneous candidiasis following the application of the antimycotic. Amorolfine was used because of its effectiveness in the topical therapy of superficial mycoses caused by yeasts and dermatophytes and its high affinity to stratum corneum and nails (12,13).…”
Section: Discussionmentioning
confidence: 99%